2015
DOI: 10.1093/alcalc/agv067
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Price Changes in Washington Following the 2012 Liquor Privatization

Abstract: Our findings indicate that liquor prices in Washington increased substantially after privatization and as compared to price changes in bordering states, with a much larger increase seen for the 750 ml size and with wide variation across store types. However, persistent drinkers looking for low prices will be able to find them in certain stores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…Furthermore, those who reported that I-1183 has not been a success were more likely to report that the number of liquor stores should be decreased, which again suggests that the increased availability of spirits may affect opinions regarding privatization. Surprisingly, opinions on taxes did not appear to affect wanting to change one's vote or thinking that I-1183 has been a success, even though spirits prices have increased by 5%-15% since privatization went into effect (Kerr et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Furthermore, those who reported that I-1183 has not been a success were more likely to report that the number of liquor stores should be decreased, which again suggests that the increased availability of spirits may affect opinions regarding privatization. Surprisingly, opinions on taxes did not appear to affect wanting to change one's vote or thinking that I-1183 has been a success, even though spirits prices have increased by 5%-15% since privatization went into effect (Kerr et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…Surprisingly, thinking that spirits taxes should be reduced (or increased) was not associated with voting regrets. Prices were found to rise after privatization (Kerr et al, 2015), and it seems likely that at least some voters would have expected reduced prices. In general, results indicate that improving the accuracy of predictions regarding the situation expected to occur after privatization could reduce support for spirits-sale privatization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) The study also found wide variation by brand and store type with cases ranging from reductions in price of over 25% to increases of over 60%. These price changes contrast with relative stability in the neighboring states of Oregon and Idaho, where average price increases were 1.9% and 1% respectively for the 750ml size and 5.5% and 1.8% respectively for the 1.75L size.…”
Section: Introductionmentioning
confidence: 82%
“…(13) This small price difference is accompanied by substantially higher revenues from spirits in control states, (2) consistent with our group's finding that liquor prices increased after the privatization in Washington where taxes were implemented to maintain revenues from liquor sales. (1) While there is strong evidence that higher prices are associated with reduced alcohol consumption and related outcomes, they also spur efforts by drinkers to avoid reducing consumption such as quality downgrading, context shifting and cross-border purchasing. (12, 14, 15) Meta-analyses from 112 studies confirm that there are negative relationships between alcoholic beverage prices and alcohol consumption, including heavy drinking.…”
Section: Discussionmentioning
confidence: 99%